Red head syndrome in shrimp aquaculture: Prevention and control - Tamadoni Jahromi S; Nazemi M; Noora Barzkar; Alboofetileh M.; Nahavandi R.; Jafari H.; Amini Khoei Z.; Rameshi H.; Pazir M.Kh.; Pourmozaffar S. (Green Wave Publication, 2025)
Red head syndrome (RHS) is an emerging concern in shrimp aquaculture, particularly affecting white leg shrimp (Lito Penaeus vannamei). Characterized by orange to red discoloration of the cephalothorax, RHS reduces marketability and leads to economic losses, especially for head -on shrimp. Although RHS doesn't affect shrimp safety or taste, it negatively impacts perceived quality and increases export rejection rates. Environmental stressors, poor farming and harvesting practices, and inadequate cold chain management are the primary factors inducing RHS. Oxidative stress, increase by elevated water temperatures, low dissolved oxygen levels, and suboptimal nutrition, drives pigment production and causes hepatopancreatic damage. This review examines the physiological, genetic, and pathological factors contributing to RHS and proposes preventative strategies. Maintaining optimal pond conditions, implementing antioxidant supplementation, improving harvesting techniques, and genetic selection are essential for mitigating RHS and enhancing shrimp quality. An integrated approach can reduce the incidence of RHS, thereby improving profitability and ensuring the sustainability of shrimp aquaculture.